HUBUNGAN PAJANAN PESTISIDA SEBELUM MASA KEHAMILAN DENGAN KEJADIAN HIPERTENSI PADA IBU HAMIL DI WILAYAH PERTANIAN KECAMATAN SUMOWONO KABUPATEN SEMARANG - Dwi Septiana; Suhartono Suhartono; Nikie Astorina Yunita Dewanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
The use of pesticides in Sumowono District was based on a statement by the Agricultural Extension Center that was not according to the correct dosage and regulations. The practice of mixing pesticides and the high frequency of pesticide use is detrimental to women who are involved in agricultural activities with the potential for long-term exposure to pesticides, which can cause health problems during pregnancy, hypertension during pregnancy. Hypertension is the main priority disease in Sumowono District. Hypertension is a major health problem during pregnancy, causing 2-3% of complications in pregnancy. The Purpose of the study was to analyze the relationship of pesticide exposure before pregnancy with hypertension in pregnant women in the agricultural area of Sumowono sub-district, Semarang district. This research is a analysis with a case control study design. The sample of this study was 102 respondents with a case sample of 34 respondents and a control sample of 68 respondents. Data analysis used the chi-square test and T-test. The results of the relationship analysis showed that work was related to pesticides (p = 0,011), pesticide exposure period (p = 0,008), length of pesticide exposure (p = 0,008), frequency of pesticide use (p = 0,002), pesticide mixing practices (p = 0,01), use of Apersonal protective equipment (p = 0,007) associated with the incidence of hypertension in pregnancy. This study recommends stopping the practice of mixing pesticides and reducing the length of time working in agricultural areas and the use of personal protective equipment standards to avoid pesticide exposure.